Metallurgical and mechanical characterization of dissimilar welds of austenitic stainless steel and super-duplex stainless steel – A comparative study. (August 2015) - Devendranath Ramkumar, K.; Singh, Anshuman; Raghuvanshi, Shubham; Bajpai, Ankur; Solanki, Tathagat; Arivarasu, M.; Arivazhagan, N.; Narayanan, S.
Abstract: This study reports the joining of dissimilar combinations of austenitic stainless steel, AISI 316L and super-duplex stainless steel (UNS S32750) by continuous current (CC) and pulsed current (PC) gas tungsten arc welding (GTAW) using ER2553 and ERNiCrMo-3 fillers. Interfacial and weld zone microstructures were examined using both optical and scanning electron microscopy (SEM) techniques. Secondary phases enriched with Nb and Mo was observed at the fusion zone of both CCGTA and PCGTA weldments employing ERNiCrMo-3. Balanced ferrite–austenite ratio was observed at the fusion zone of ER2553 weldments. Tensile studies connoted that the fracture occurred at the parent metal of AISI 316L in all the cases. It was inferred from the impact studies that the PCGTA weldments employing ER2553 filler exhibited greater toughness of 189 J. Bend test results showcased that both CCGTA and PCGTA weldments employing ERNiCrMo-3 acquainted for better ductility.